Evaluation of goat ovaries and follicles by histological study - Shathi, SJ; Khandoker, MAMY; Debnath, S; Mahzabin, R; Jahan, MA; Islam, MR; Khatun, A (Bangladesh Journal of Animal Science, 2022)
The present study evaluated slaughterhouse goat ovaries and follicles to know the effect of corpus luteum on the number and quality of ovarian follicles. For this study, 18 goat ovaries were collected and categorized as ovaries with corpus luteum (CL+) and without corpus luteum (CL–) group. Both groups were evaluated by morphometric measurements and histological observation. Among 18 ovaries, 12 ovaries contained CL (66.67%) and 6 ovaries were without CL (33.33%). Based on the morphometric measurements, the length and weight of the ovaries with CL were numerically higher (p>0.05) than those of the ovaries without CL. But the diameter of the ovaries with CL was significantly higher (p<0.05) than those of the ovaries without CL. In comparison to the CL– group, the CL+ group had a numerically higher (p>0.05) number of follicles with a diameter of 2-6 mm and > 6 mm. Histological analysis revealed that the total number of follicles (primary to antral) in CL– group (11.10±2.47) was numerically higher (p>0.05) than that of the CL+ group (10.07±2.47). Presence of primary (4.44±1.59), secondary (1.45±0.83) and antral (6.27±1.31) follicles were found higher (p>0.05) in ovaries without CL than that of with CL (4.05±1.61, 0.92±0.21, 5.08±1.21 respectively). On the other hand, the number of degenerated primary (1.29±0.56), secondary (0.52±0.14) and antral (3.38±0.66) follicles were found comparatively higher (p>0.05) in the ovaries with CL than that of the ovaries without CL (1.14±0.69, 0.37±0.19, 2.40±0.40 respectively). Since, there was no statistical difference found among the number of total and different types of follicles between ovaries with or without corpus luteum; hence, it may be summarized that both type of ovaries may be used for the retrieval of oocytes for further reproductive biotechnological study. Bangladesh Journal of Animal Science, 51 (4): 145-151